High-strength abrasion-resistant martensitic stainless steel material and preparation method thereof
By adding Cu, Al and Ni elements to martensitic stainless steel and controlling the heat treatment process, the nano-scale precipitation phase is prepared, which solves the problems of insufficient strength and low toughness in the hydropower industry, and significantly improves the strength and wear resistance of the material.
Patent Information
- Application Number
- CN202510143811.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-10
- Publication Date
- 2025-04-15
AI Technical Summary
Due to insufficient strength and low toughness in the hydropower industry, the existing 04Cr13Ni5Mo stainless steel is difficult to meet the comprehensive mechanical performance requirements of key components of generator sets under high load conditions. At the same time, wear and cavitation are prone to occur in high-speed erosion water flow environments.
Nano-scale precipitation phases are prepared by adding Cu, Al and Ni elements to martensitic stainless steel and controlling the heat treatment process to improve the strength and wear resistance of the material.
It significantly improves the strength and crack resistance of martensitic stainless steel, enhances its corrosion resistance and wear resistance, and meets the demand for high-strength and high-toughness materials in the hydropower industry.
Smart Images

Figure CN119824337A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of research and development of new stainless steel materials, and in particular to a high-strength and wear-resistant martensitic stainless steel material and a preparation method thereof. Background Art
[0002] Martensitic stainless steel materials are widely used in the manufacture of knives, medical equipment, petrochemical equipment, hydropower equipment, etc. due to their high strength, corrosion resistance and excellent welding performance. 04Cr13Ni5Mo stainless steel is a martensitic stainless steel with a low carbon content. Its corrosion resistance and welding performance are better than other high-carbon martensitic stainless steels, and it has higher impact toughness, but its strength is relatively low. This stainless steel material is widely used in the hydropower industry due to its good plasticity, toughness, weldability and corrosion resistance. However, due to the increasing design capacity of the units of various power stations at this stage, the key components of the generator set are forced to bear greater loads during operation, which in turn puts higher requirements on the comprehensive mechanical properties of these component materials.
[0003] At present, the 04Cr13Ni5Mo stainless steel used in the hydropower industry has enough toughness but insufficient strength. Although the strength of high-carbon stainless steel can meet the requirements, the toughness will be significantly reduced. At present, the industry usually adopts the method of increasing the volume of components to increase their strength and rigidity to meet the mechanical performance requirements. However, this will seriously increase the instability of the mechanism and reduce the power generation efficiency of the power station. Therefore, exploring high-strength and toughness alloys is currently a key issue for the hydropower equipment industry.
[0004] In addition, hydropower components have been in service for a long time in a high-speed water flow environment, and wear and cavitation are the two main mechanisms of material loss. The cause of wear is that the material hardness is not enough. When the component surface is impacted by the sediment in the water flow, the surface material of the component will be cut and worn by the sediment particles. The cause of cavitation is that the material is not strong enough. When the water flow impacts the component, a cavitation effect will be generated to form bubbles. When the bubbles are annihilated, a high-pressure water flow will impact the material. Therefore, under the long-term cavitation effect of the water flow, the surface of the component will crack and cavitation due to fatigue. Under the combined effect of wear and cavitation, material loss is aggravated. When the component material is severely abraded, it usually causes the surface contour of the hydropower component to be damaged, thereby affecting the force of the water flow and further affecting the mechanical stability of the entire generator set; when the abrasion is severe, it may even cause the component to be suddenly destroyed during operation, resulting in major safety accidents.
[0005] Therefore, it is necessary to develop a high-strength and wear-resistant martensitic stainless steel to address the deficiencies of the prior art and to solve or alleviate one or more of the above problems. Summary of the invention
[0006] The object of the present invention is to provide a high-strength and wear-resistant martensitic stainless steel material and a preparation method thereof in view of the above-mentioned problems, by adding Cu, Al and Ni elements to the martensitic stainless steel and controlling the heat treatment process to prepare a nano-scale precipitated phase, so as to improve the strength, toughness and wear resistance of traditional stainless steel.
[0007] The technical solution adopted by the present invention is as follows: a high-strength and wear-resistant martensitic stainless steel material, the preparation of which includes the following elements in mass percentage:
[0008] C (0-0.03%); Cr (11.5%-14.0%); Ni (7.5%-9.5%); Cu (1.0%-2.5%); Nb (0.3%-0.6%); Ti (0.5%-1.4%); Mo (0.1%-0.3%); Mn (0.1%-0.3%); Si (0.1%-0.3%); Al (0.1%-0.3%); P (0-0.04%); S (0-0.03%); O (0-0.04%); N (0-0.04%); the rest are Fe and unavoidable impurity elements.
[0009] Furthermore, the preparation of the martensitic stainless steel material includes the following elements in percentage by mass:
[0010] C: 0.02%; Cr: 12.5%; Ni: 8.6%; Cu: 1.5%; Nb: 0.5%; Ti: 0.8%; Mo: 0.23%; Mn: 0.24%; Si: 0.27%; Al: 0.15%; P: 0.009%; S: 0.005%; O: 0.023%; N: 0.007%, of which P, S, N are impurity elements and the rest is Fe.
[0011] A preparation method for the high-strength and wear-resistant martensitic stainless steel material comprises the following steps:
[0012] S1: preparing raw materials according to proportions, pre-treating the raw materials, and putting the pre-treated raw materials into a smelting furnace for high-temperature melting to form alloy liquid;
[0013] S2: Casting the alloy liquid into an alloy ingot, and subjecting the alloy ingot to high temperature forging to form a plate;
[0014] S3: hot rolling the plate to form a rolled plate;
[0015] S4: homogenizing the rolled plate;
[0016] S5: The homogenized plate is subjected to solution treatment in an environment 50 to 100°C higher than the austenitizing temperature (Ac3) of the stainless steel;
[0017] S6: The plate after solution treatment is aged at a temperature lower than the initial temperature of austenite transformation (Ac1) to finally obtain a high-strength and wear-resistant martensitic stainless steel material.
[0018] Further, in step S1: pretreatment includes removing impurities, classifying and weighing the raw materials.
[0019] Furthermore, before step S2, the alloy liquid needs to be refined to remove impurities and bubbles in the alloy liquid.
[0020] Further, in step S2, the forging temperature ranges from 900°C to 1200°C, and the cooling method is air cooling.
[0021] Further, in step S3, the rolling temperature range is 900° C. to 1200° C., and the cooling method is air cooling.
[0022] Furthermore, in step S4, the temperature of the homogenization treatment is 1200° C., the holding time is 24 hours, and the cooling method is water cooling.
[0023] Further, in step S5, the temperature range of the solution treatment is 800° C. to 850° C., the holding time is 0.5 to 1 h, and the cooling method is oil cooling.
[0024] Further, in step S6, the temperature range of the aging treatment is 460°C to 480°C, the aging time is 3h to 4h, and the cooling method is air cooling.
[0025] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0026] The present invention prepares nano-scale precipitation phase by adding Cu, Al and Ni elements to martensitic stainless steel and controlling the heat treatment process, so as to improve the toughness and wear resistance of traditional stainless steel. In addition, through heat treatment, phase transformation stress is generated in the martensitic phase transformation process, thereby introducing a large number of small-angle grain boundaries in the material matrix. The interface energy of these small-angle grain boundaries is several orders of magnitude lower than that of ordinary grain boundaries. On the one hand, the formation of intergranular corrosion channels is avoided, thereby improving the corrosion resistance of the material. On the other hand, a position can be provided for the nucleation of nano-precipitated phases, avoiding the segregation of precipitated phases to grain boundaries, thereby improving the strength and crack resistance sensitivity of martensitic stainless steel. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The present invention will now be described by way of example with reference to the accompanying drawings, in which:
[0028] Figure 1 EBSD analysis results of the martensitic stainless steel material disclosed in the present invention;
[0029] Figure 2 The energy spectrum analysis result of the martensitic stainless steel material disclosed in the present invention;
[0030] Figure 3 The high-resolution energy spectrum analysis result of the martensitic stainless steel material disclosed in the present invention;
[0031] Figure 4 is the tensile stress-strain curve of the martensitic stainless steel material disclosed in the present invention;
[0032] Figure 5 The fracture morphology of the tensile specimen of the martensitic stainless steel material disclosed in the present invention. DETAILED DESCRIPTION
[0033] In the description of this specification, it should be noted that if the terms "center", "up", "down", "left", "right", "vertical", "horizontal", "inside", "outside", etc. appear, the orientation or position relationship indicated is based on the orientation or position relationship shown in the drawings, or is the orientation or position relationship in which the product of this specification is usually placed when used. It is only for the convenience of describing this specification and simplifying the description, and does not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on this specification.
[0034] In addition, if the terms "horizontal" or "vertical" appear in the description of this specification, it does not mean that the components are required to be absolutely horizontal or suspended, but can be slightly tilted. For example, "horizontal" only means that its direction is more horizontal than "vertical", and does not mean that the structure must be completely horizontal, but can be slightly tilted.
[0035] In the description of this specification, it should also be noted that, unless otherwise clearly stipulated and limited, the terms "set", "installed", "connected" and "connected" should be understood in a broad sense. For example, the connection can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, and it can be a connection between the internal parts of two elements.
[0036] Example 1
[0037] like Figure 1 As shown, a high-strength and wear-resistant martensitic stainless steel material, the preparation of the martensitic stainless steel material includes the following elements in mass percentage:
[0038] C (0-0.03%); Cr (11.5%-14.0%); Ni (7.5%-9.5%); Cu (1.0%-2.5%); Nb (0.3%-0.6%); Ti (0.5%-1.4%); Mo (0.1%-0.3%); Mn (0.1%-0.3%); Si (0.1%-0.3%); Al (0.1%-0.3%); P (0-0.04%); S (0-0.03%); O (0-0.04%); N (0-0.04%); the rest are Fe and unavoidable impurity elements.
[0039] In this embodiment, the content of Ni element is increased in the martensitic stainless steel material, and Ni element can form a precipitation strengthening phase of Ni3Ti with Ti element to achieve precipitation strengthening effect; Ni is the main austenite forming element, and increasing Ni content significantly increases the toughness of stainless steel; in addition, Ni and Fe can be infinitely dissolved, and increasing Ni content can significantly enhance the effect of solid solution strengthening, thereby enhancing strength; more importantly, the critical transition temperature of steel and the diffusion rate of each element in steel are reduced under the action of Ni element, thereby significantly increasing hardenability, which is conducive to obtaining a uniform martensitic structure.
[0040] In this embodiment, Cu and Al elements are added to the martensitic stainless steel material to form a nano-scale dispersion strengthening phase of Al2Cu, thereby making the aging structure more uniform, improving both strength and plasticity. In addition, Cu can reduce the potential difference between the grain boundary and the grain, and significantly improve the corrosion resistance of stainless steel to non-oxidizing acids, thereby reducing the sensitivity of martensitic stainless steel to pitting corrosion. In addition, after adding Al elements, it is easier to form nano-particle phases of Ni3Al and NiAl in stainless steel, thereby improving the wear resistance and cavitation erosion resistance of the alloy.
[0041] In this embodiment, Ti and Nb elements are added to the martensitic stainless steel material, and the intergranular corrosion resistance of the steel and the high temperature strength and wear resistance of the stainless steel are improved.
[0042] In this embodiment, the strengthening elements of Mn and Mo are added to the martensitic stainless steel matrix, so that the strength of the stainless steel matrix is improved. In addition, Mo is a strong carbide-forming element, and the formed carbides are extremely stable, which can prevent the grain growth of austenite when heated, reduce the overheating sensitivity of steel, further refine the grains, and improve the strength and toughness at the same time. In addition, the molybdenum element can make the passive film in the stainless steel more dense and firm, thereby effectively improving the abrasion resistance of the stainless steel.
[0043] In summary, this embodiment increases the Ni content on the basis of the original martensitic stainless steel, adds alloying elements such as Al and Cu, forms a large number of dispersed nano-precipitated phase particles, significantly improves the strength of the martensitic stainless steel, and also retains a certain toughness. Adding alloying elements such as Mn, Ti, and Nb improves the wear resistance of the martensitic stainless steel.
[0044] Example 2
[0045] Based on Example 1, a specific implementation method that can be implemented is further proposed.
[0046] The preparation of the martensitic stainless steel material includes the following elements in percentage by mass:
[0047] C: 0.02%; Cr: 12.5%; Ni: 8.6%; Cu: 1.5%; Nb: 0.5%; Ti: 0.8%; Mo: 0.23%; Mn: 0.24%; Si: 0.27%; Al: 0.15%; P: 0.009%; S: 0.005%; O: 0.023%; N: 0.007%, of which P, S, N are impurity elements and the rest is Fe.
[0048] Example 3
[0049] A preparation method is provided for preparing the high-strength and wear-resistant martensitic stainless steel material described in Example 1, especially for preparing the high-strength and wear-resistant martensitic stainless steel material described in Example 2, comprising the following steps.
[0050] S1: Prepare raw materials according to proportion, pre-treat the raw materials, remove impurities, classify and weigh the raw materials; put the pre-treated raw materials into a smelting furnace for high-temperature melting to form alloy liquid; refine the alloy liquid to remove impurities and bubbles in the alloy liquid.
[0051] S2: Casting the alloy liquid into alloy ingots, and subjecting the alloy ingots to high-temperature forging to form plates, the thickness of the plates being 30 mm; the forging temperature range is 900° C. to 1200° C., and the cooling method is air cooling.
[0052] S3: hot rolling the plate to form a rolled plate; the rolling temperature range is 900° C. to 1200° C., and the cooling method is air cooling.
[0053] S4: homogenizing the rolled plate; the homogenizing temperature is 1200° C., the holding time is 24 hours, and the cooling method is water cooling.
[0054] S5: The homogenized plate is subjected to solution treatment in an environment 50 to 100°C higher than the austenitizing temperature (Ac3) of stainless steel; the temperature range of the solution treatment is 800°C to 850°C, the holding time is 0.5□1h, and the cooling method is oil cooling.
[0055] S6: The plate after solution treatment is aged at a temperature lower than the initial temperature of austenite transformation (Ac1), and finally a high-strength and wear-resistant martensitic stainless steel material is obtained; the temperature range of aging treatment is 460℃~480℃, the aging time is 3h~4h, and the cooling method is air cooling.
[0056] In this example, the martensitic stainless steel material is analyzed as follows.
[0057] 1. Grain Characterization Analysis: Gemini SEM300 field emission scanning electron microscope was used to characterize the phase and grain structure of the embodiment. The characterization results are shown in the attached Figure 1 As shown, the collection area is 200×160μm. Figure 1 (a) in the figure. Figure 1 In the (c) panel, the phase composition of the heat-treated martensitic stainless steel obtained by EBSD is: 99.2% martensite, 0.4% austenite, and 0.3% Ni3Ti. The orientation imaging map is constructed based on the grain Kikuchi line contrast BC (Band Contrast) information, as shown in the figure. Figure 1 In the (d) panel, the red lines represent small-angle grain boundaries of 2°-15°, accounting for 61%, and the white lines represent large-angle grain boundaries greater than 15°, accounting for 39%, indicating that the orientation difference between adjacent grains is small, and dislocations move through adjacent grains, causing local slip and easily increasing local dislocation density. Figure 1 In the (e) panel, the grain orientation distribution diagram shows that the results of the Euler angle representation of the grain orientation have large color differences, and there are penetration, bite, and interaction between the grains. It is speculated that this leads to the high strength and toughness of the martensitic stainless steel after heat treatment. Figure 1 As shown in panel (f), the mean grain size of the stainless steel is 3.4 μm, the minimum is 1.1 μm, the maximum is 37.2 μm, and the standard deviation is 4.0 μm.
[0058] 2. Strengthening phase analysis: The composition characteristics of the martensitic stainless steel were analyzed by using the Oxford energy spectrum analyzer X-Max 50 equipped with a Gemin iSEM300 field emission scanning electron microscope. The image acquisition area was 200×160μm. The energy spectrum analysis structure was as follows: Figure 2 As shown. Figure 2It can be seen that the main elements Fe, Cr, and Ni of the martensitic stainless steel are very evenly distributed without obvious enrichment; the key elements Cu, Al, and Ti have a small amount of precipitation, which plays a role in precipitation strengthening. The precipitates of Ti and Al are larger in size, and it is obvious that there is a small amount of enrichment. The previous EBSD characterization has proved that the enrichment of the Ti element forms the Ni3Ti precipitation phase; the Al-containing precipitate phase and the copper-rich phase precipitate are smaller in size and need to be further confirmed by transmission electron microscopy (TEM). The precipitates were observed at high magnification using a Tecnai G2 F30 field emission transmission electron microscope, and the enrichment of the key strengthening elements was checked by EDS surface scanning. The EDS energy spectrum surface scanning results are shown as follows. Figure 3 As shown. Figure 3 Nanoscale (1-15nm) and dispersed copper-rich phase precipitates can be clearly seen. In addition, the enrichment of Ni and Al elements can be clearly seen, indicating that nanoscale strengthening phases of Ni3Al or NiAl are also formed on the martensitic stainless steel matrix. These dispersed nano-precipitation strengthening phases play a vital role in improving the wear resistance of the material.
[0059] 3. Mechanical properties analysis: According to the relevant provisions of "GB / T228.1-2010 Metallic Materials Tensile Test Part 1: Room Temperature Test Method" for tensile tests, combined with the research content, a tensile test plan was formulated. The geometric parameters of the tensile specimen are: length 30mm, width 7mm, thickness 1.5mm, gauge length 12mm; tensile test speed 1mm / min, the true stress-strain curve obtained by the tensile test is as follows Figure 4 As shown in the figure, it can be seen that the yield strength of the martensitic stainless steel can reach 1349MPa, and the tensile strength can reach 1374MPa; and the material closest to the high-strength and wear-resistant martensitic stainless steel material proposed in this embodiment is 04Cr13Ni5Mo ultra-low carbon martensitic stainless steel, whose material composition is: C 0.05max; Si 0.60max; Mn 0.50-1.00; P / S 0.030; Cr 11.50-14.00; Ni 2.50-5.50; Mo 0.50-1.10. Its tensile strength is 795MPa; yield strength is 620MPa; it can be seen that the high-strength and wear-resistant martensitic stainless steel material proposed in the embodiment has significant yield strength and tensile strength advantages. Figure 5 This is the fracture morphology of the tensile specimen. As can be seen from the figure, the macroscopic fracture morphology of the specimen shows obvious cracks, and the microscopic fracture morphology shows obvious dimples of varying sizes and depths, indicating that although the martensitic stainless steel has high hardness / strength, it also has certain toughness.
[0060] In summary, by controlling the heat treatment system during the preparation of martensitic stainless steel materials, a large number of small-angle grain boundaries are produced, thereby achieving an interface strengthening effect and providing favorable conditions for the precipitation of nano-precipitation phases.
[0061] The present invention is not limited to the above-mentioned specific embodiments, but extends to any new features or any new combination disclosed in this specification, as well as any new method or process steps or any new combination disclosed.
Claims
1. A high-strength and wear-resistant martensitic stainless steel material, characterized in that: The preparation of the martensitic stainless steel material includes the following elements in percentage by mass: C (0-0.03%); Cr (11.5%-14.0%); Ni (7.5%-9.5%); Cu (1.0%-2.5%); Nb (0.3%-0.6%); Ti (0.5%-1.4%); Mo (0.1%-0.3%); Mn (0.1%-0.3%); Si (0.1%-0.3%); Al (0.1%-0.3%); P (0-0.04%); S (0-0.03%); O (0-0.04%); N (0-0.04%); the rest are Fe and unavoidable impurity elements.
2. The martensitic stainless steel material according to claim 1, characterized in that: The preparation of the martensitic stainless steel material includes the following elements in percentage by mass: C: 0.02%; Cr: 12.5%; Ni: 8.6%; Cu: 1.5%; Nb: 0.5%; Ti: 0.8%; Mo: 0.23%; Mn: 0.24%; Si: 0.27%; Al: 0.15%; P:0.009%; S: 0.005%; O: 0.023%; N: 0.007%, of which P, S, and N are impurity elements, and the rest is Fe.
3. A preparation method for preparing the high-strength and wear-resistant martensitic stainless steel material according to any one of claims 1 to 2, characterized in that: The following steps are involved: S1: preparing raw materials according to proportions, pre-treating the raw materials, and putting the pre-treated raw materials into a smelting furnace for high-temperature melting to form alloy liquid; S2: Casting the alloy liquid into an alloy ingot, and subjecting the alloy ingot to high temperature forging to form a plate; S3: hot rolling the plate to form a rolled plate; S4: homogenizing the rolled plate; S5: The homogenized plate is subjected to solution treatment in an environment 50 to 100°C higher than the austenitizing temperature (Ac3) of the stainless steel; S6: The plate after solution treatment is aged at a temperature lower than the initial temperature of austenite transformation (Ac1) to finally obtain a high-strength and wear-resistant martensitic stainless steel material.
4. The preparation method according to claim 3, characterized in that: In step S1: pre-processing includes removing impurities, sorting and weighing the raw materials.
5. The preparation method according to claim 3, characterized in that: Before step S2, the alloy liquid needs to be refined to remove impurities and bubbles in the alloy liquid.
6. The preparation method according to claim 3, characterized in that: In step S2, the forging temperature ranges from 900°C to 1200°C, and the cooling method is air cooling.
7. The preparation method according to claim 3, characterized in that: In step S3, the rolling temperature range is 900°C to 1200°C, and the cooling method is air cooling.
8. The preparation method according to claim 3, characterized in that: In step S4, the temperature of the homogenization treatment is 1200° C., the holding time is 24 hours, and the cooling method is water cooling.
9. The preparation method according to claim 3, characterized in that: In step S5, the temperature range of the solution treatment is 800°C to 850°C, the holding time is 0.5 to 1 hour, and the cooling method is oil cooling.
10. The preparation method according to claim 3, characterized in that: In step S6, the temperature range of the aging treatment is 460°C to 480°C, the aging time is 3h to 4h, and the cooling method is air cooling.
Citation Information
Cited By
Iron-based wear-resistant corrosion-resistant coating for marine environment and preparation method of iron-based wear-resistant corrosion-resistant coating
CN121065692A